A benefit–risk analysis of natalizumab in the treatment of patients with multiple sclerosis when considering the risk of progressive multifocal leukoencephalopathy. (April 2014) - Walker, Anna; Watson, Crystal; Alexopoulos, Stamatia T.; Deniz, Baris; Arnold, Ryan; Bates, David
Abstract Background: Natalizumab is a highly effective treatment for patients with relapsing–remitting multiple sclerosis (RRMS). Treatment with natalizumab has been associated with progressive multifocal leukoencephalopathy (PML), a rare yet serious disease of the brain. Published studies have quantified the PML risk by the presence of anti-JC virus antibodies, previous immunosuppressant use, and duration of natalizumab treatment. Objectives: The aim of this analysis was to evaluate the net benefits and risks for patients with RRMS receiving natalizumab treatment compared with fingolimod, interferon-β, and no treatment across PML risk sub-groups. Research design and methods: Based on previously validated MS model structures, a Markov cohort model was developed to assess the impact of treatment on quality-adjusted life years (QALYs). Natalizumab-treated patients were classified by PML risk sub-groups and analysed separately for short-term (2 years) and long-term (20 years) time horizons. Main outcome measures: Main outcome measures included total QALYs by PML risk sub-group and the increase in PML risk associated with natalizumab treatment which offsets the quality of life benefit of comparator treatments. Results: Results showed higher QALYs with natalizumab versus all other comparators across PML risk sub-groups over both time horizons. For the QALYs of natalizumab to equal the QALYs of fingolimod, interferon-β, and no treatment, the risk of PML would have to increase 4.6–84.2 times, 24.0–444.3 times, and 5.7–106.1 times, respectively (short term), and 1.4–123.4 times, 1.5–138.3 times, and 2.2–193.7 times, respectively (long term). Conclusion: This study shows that natalizumab generates the most net health benefits in terms of quality-adjusted life years compared with fingolimod, interferon-β, or no treatment, even when the risk of natalizumab-associated PML is taken into consideration. This study is limited by the availability of published data around natalizumab-associated PML, as well as the constraints of the model used to conduct the analysis.